2015
DOI: 10.1080/13607863.2014.1003280
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among depressive, passive-aggressive, sadistic and self-defeating personality disorder features with suicidal ideation and reasons for living among older adults

Abstract: These findings suggest that depressive PD features are strongly related to increased suicidal thinking and lowered resilience to suicide among older adults. Assessment of depressive PD features should also be especially included in the assessment of later-life suicidal risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…In addition, the Lausanne Study indicated a 1.3 male to female ratio for the prevalence of suicide in former inpatients with personality disorders ( 37 ), and Harwood and colleagues’ psychological autopsy study did not find a significant gender difference in personality disorder rates ( 45 ). The majority of case–control studies included in the review controlled for the potential effect of gender, with only four that did not, or for which this information was missing ( 40 , 47 , 65 , 66 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the Lausanne Study indicated a 1.3 male to female ratio for the prevalence of suicide in former inpatients with personality disorders ( 37 ), and Harwood and colleagues’ psychological autopsy study did not find a significant gender difference in personality disorder rates ( 45 ). The majority of case–control studies included in the review controlled for the potential effect of gender, with only four that did not, or for which this information was missing ( 40 , 47 , 65 , 66 ).…”
Section: Resultsmentioning
confidence: 99%
“…11 This may be partially explained by the finding that older adults with personality disorders, particularly if multiple, tend to have a worse self-perceived quality of life than others within their cohort, including those who may also be known to secondary mental health services themselves. 12 Suicidal ideation itself has been found to be one of the best predictors of completed suicide in this population and it has been hypothesised that maladaptive coping, which is often seen as a feature in personality disorders, significantly predicts this risk also.…”
Section: Clinical Presentation Of Personality Disorders In Older Adultsmentioning
confidence: 97%
“…Previous studies have shown the association between PSD and psychiatric disorders included antidepressant-related sexual dysfunctions patients with depressive or anxiety disorders [9, 23-25], female paraphilia focused and the personality disorders on the forensic psychiatric topics [7,8], and the FTM gender disorders and depression, post-traumatic stress disorder, anxiety disorders and suicides [5,6,26]. However, these studies were mostly conducted in cross-section methods, and our study is unique for the retrospective cohort design, from a larger population-based database.…”
Section: Comparison Of This Study To Previous Literaturesmentioning
confidence: 99%
“…Several studies have found the mutual relations between the psychiatric comorbidity and PSD [4][5][6][7][8][9]. For the clinicians, it is essential to understand the mutual relationship between female patients with PSD and their psychiatric morbidity.…”
Section: Introductionmentioning
confidence: 99%